Education and Application of Digital Media in Creation and Documentation Artery Based Service Letter - Amir, Amril; Afnita, Afnita; Zuve, Farel Olva; Erlianti, Gustina (JERIT: Journal of Educational Research and Innovation Technology, 2024)
This activity aims to provide an understanding of the application of digital media in creating and documenting official letters carried out at SMPN Padang Pariaman Regency. Based on observations, it is known that the structure and language used in official letters are still not in accordance with Indonesian language rules. Apart from that, it was also found that the preparation and storage of archives within the school was still inadequate. School archives or documents are arranged in cabinets, so it takes a long time to find them, and they are not well maintained due to improper arrangement and storage. Therefore, an activity is needed to correct errors in writing official letters and documenting existing school archives. Based on this explanation, it is necessary to carry out training activities regarding the creation and documentation of digital-based official letters using the Arteri application at State Middle Schools in Padang Pariaman Regency, West Sumatra. The research results show that in letter writing activities, it is important to know the structure and language of the letter so that it becomes easier to write a good and correct letter. Apart from that, documenting letters is important because it refers to the current digital era, so other roles are needed for changing times. By utilizing technology that will make the documentation process easier.